Marketing Communication as a Moderate Variable Between Consumer Experience and Trust to Grab Service User Loyalty in Makassar City - Ihwan Ihwan (State Islamic Institute of Bone, Indonesia, 2021)
Marketing Communication as a Moderation Variable between Experience and Consumer Trust Toward loyalty of Grab Service Users in Makassar City. This research aims to analyze and describe the influence of consumer experience on consumer loyalty, the influence of consumer confidence on customer loyalty, the influence of consumer experience on consumer loyalty moderated by marketing communication, and the influence of consumer trust on consumer loyalty moderated by marketing communication. This research was conducted in Makassar City. Data collection is done though documentation and interviewing respondents using a questionnaire. The number of respondents in this research was 134. Data were analyzed by using descriptive statistical analysis with multiple linear regression analysis methods through SPSS version 25. The results of this research indicate that consumer experience has no influence on consumer loyalty, as evidenced in the output showing a significance value of 0.380 0.05 and T-count of 0.882 Table 1.978. in contrast to consumer confidence which has an influence on consumer loyalty, it is evident that the output shows a significance value of 0.000 0.05 and a T-count of 6.599 T-table 1.978. then the consumer experience still has no influence even though moderated by marketing communication, it is proven that the output shows a significance value of 0.822 0.05 and F-count value of 0.225 F-table 1.978. while consumer confidence still has an influence on consumer loyalty with moderated marketing communication, it is proven that the output shows a significance value of 0.000 0.05 and F-count 4.429 F-table 1.978.